PENGARUH JARAK DARI SALURAN DRAINASE TERHADAP FLUKTUASI MUKA AIR TANAH DAN SIFAT FISIK TANAH GAMBUT PEDALAMAN DI TUMBANG NUSA - KALIMANTAN TENGAH: THE IMPACT OF DISTANCE FROM DRAINAGE CHANNELS ON GROUNDWATER LEVEL FLUCTUATIONS AND PHYSICAL PROPERTIES OF INLAND PEAT SOILS IN TUMBANG NUSA, CENTRAL KALIMANTAN - Adji, Fengky Florante; Hutahaean, Sri Devi; Melhanah, Melhanah; Amelia, Vera (AgriPeat, 2024)
Indonesia is a country that has the largest peat area in the tropics, estimated at 21 million ha. This research aims to determine the effect of the distance from the drainage channel on fluctuations in groundwater levels (water table) and physical properties of peat soil in different land cover conditions with open land planted with Rambutan trees (N. lappaceum) and bush land growing ferns (Pteridophyta) and Bajakah. (S. littoralis). This research was carried out from August to October 2023 in Tumbang Nusa Village, Jabiren Raya Subdistrict, Pulang Pisau Regency, Central Kalimantan Province and the UPT. LLG-CIMTROP Laboratory, University of Palangka Raya. Firstly take n 1 (one) whole soil sample (undisturb) and taken ± 1 kg by using a ring with a depth of 0-20 cm and measure the physical properties of the soil 4 (four) times, once every 2 (two) weeks at each sampling point peat. The method used in the research is purposive sampling, namely a sampling method with certain considerations in 4 (four) plots each with different land cover. Data is processed using Microsoft Excel 2021 for Windows which will be presented in the form of tables and graphs. The results of groundwater level measurements in the field show a weak relationship, a very weak relationship and a fairly strong relationship between the physical properties of peat soil in different land cover conditions. The relationship between ground water level (water table) and volumetric weight, water content and temperature are cubic and positive. The relationship between ground water level (water table) and particle density and humidity in different land conditions shows a negative cubic relationship. From testing the soil properties, the cumulative effect is volume weight (bulk density), temperature and water content, where the R2 value for volume weight is 0,4518 and temperature is 0,56. Then the water table is influenced by the distance from drainage canal. Keywords: Peat soil, water table, physical properties, land use, drainage canal, and environmental factors